Ergonomic work analysis application in a small shoe business - Callegaro, Aline Marian (2013)
This paper aims to presentthe results after conducting an Ergonomic Work Analysis (EWA) in a smallbusiness located in Porto Alegre. The ergonomic intervention was performed basedon Guérin et al. (2001) and aimed to analyze the process organization and thelayout of the shoemaker workstations to provide improvements to these areas.The starting point was the account of the small shoe business owner’s need hadto hire one more shoemaker without increasing the company physical space. The EWAwas used focusing the work organization, how the flow of information ran fromthe entry of an order to the final stage of the product repairing. Thediagnosis showed the company main problems were related to the shop assistantsdependence on the shoemakers to provide budget information and delivery time tocustomers and the layout organization. Among the results, a temporal analysisof two company recurrent tasks was performed in order to ascertain possiblelosses related to the displacement and the search for material. A new layoutscheme was also proposed, aiming to organize the work stations, making easierthe stock, tools and equipment removal, providing a free space to make possiblethe hiring of the new shoemakers within the current company boundaries.